A Survey of Sediment Fineness and Moisture Content in the Soyang Lake Floodplain Using GPS Data. (February 2021) - Syifa, Mutiara; Kadavi, Prima Riza; Park, Sung Jae; Lee, Chang-Wook
Abstract: Soyang Lake is the largest lake in Republic of Korea, bordering Chuncheon, Yanggu, and Inje in Gangwon Province. It is widely used as an environmental resource for hydropower, flood control, and water supply. Therefore, we conducted a survey of the floodplain of Soyang Lake to analyze the sediments in the area. We used global positioning system (GPS) data and aerial photography to monitor sediment deposits in the Soyang Lake floodplain. Data from three GPS units were compared to determine the accuracy of sampling location measurement. Sediment samples were collected at three sites: two in the eastern region of the floodplain and one in the western region. A total of eight samples were collected: Three samples were collected at 10 cm intervals to a depth of 30 cm from each site of the eastern sampling point, and two samples were collected at depths of 10 and 30 cm at the western sampling point. Samples were collected and analyzed for vertical and horizontal trends in particle size and moisture content. The sizes of the sediment samples ranged from coarse to very coarse sediments with a negative slope, which indicate eastward movement from the breach. The probability of a breach was indicated by the high water content at the eastern side of the floodplain, with the eastern sites showing a higher probability than the western sites. The results of this study indicate that analyses of grain fineness, moisture content, sediment deposits, and sediment removal rates can be used to understand and predict the direction of breach movement and sediment distribution in Soyang Lake.